Vacuum-Assisted Suction Drainage as a Successful Treatment Option for Postoperative Symptomatic Lymphoceles - Franke, Mareike; Saager, Christian; Kröger, Jan-Robert; Borggrefe, Jan; Mückner, Kersten (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose Lymphoceles often occur within several weeks or even months after surgery. Mostly asymptomatic and therefore undiagnosed, they may be self-healing without any treatment. A small percentage of postoperative lymphoceles are symptomatic with significant pain, infection, or compression of vital structures, thus requiring intervention. Many different treatment options are described in the literature, like drainage with or without sclerotherapy, embolization of lymph vessels, and surgical approaches with laparoscopy or laparotomy. Inspired by reports stating that postoperative suction drainage can prevent the formation of lymphoceles, we developed a simple protocol for vacuum-assisted drainage of symptomatic lymphoceles, which proved to be successful and which we would therefore like to present.Materials and Method Between 2008 and 2020, 35 patients with symptomatic postoperative lymphoceles were treated with vacuum-assisted suction drainage (in total 39 lymphoceles). The surgery that caused lymphocele formation had been performed between 8 and 572 days before. All lymphoceles were diagnosed based on biochemical and cytologic findings in aspirated fluid. The clinical and imaging data were collected and retrospectively analyzed.Results In total, 43 suction drainage catheters were inserted under CT guidance. The technical success rate was 100 %. One patient died of severe preexisting pulmonary embolism, sepsis, and poor conditions (non-procedure-related death). In 94.8 % of symptomatic lymphoceles, healing and total disappearance could be achieved. 4 lymphoceles had a relapse or dislocation of the drainage catheter and needed a second drainage procedure. Two lymphoceles needed further surgery. The complication rate of the procedure was 4.6 % (2/43, minor complications). The median indwelling time of a suction drainage catheter was 8–9 days (range: 1–30 days).Conclusion The positive effects of negative pressure therapy in local wound therapy have been investigated for a long time. These positive effects also seem to have an impact on suction drainage of symptomatic lymphoceles with a high cure rate.Key Points: Citation Format
Keywords: symptomatic lymphocele; negative pressure therapy; drainage; interventional procedures